EVALUATION OF ANTHELMINTIC ACTIVITY OF CITRUS RETICULATA: IN VITRO AND ITS PHYTOCHEMICAL INVESTIGATION - Aryal, Arjan; Upreti, Sabita; Das, Kuntal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Background: The prevalence of worm infestation is high in under developed and developing countries due to poor sanitation and lack of health education. Citrus reticulata, fruit belonging to citrus family rutaceae is a common fruit native to Asia. Peels of the fruit is rich in limonene, a potent phytoconstituent having anthelmintic activity. However, proper utilization of peels has not been done as it is not consumed and is therefore discarded. Objective: To explore various phytoconstituents present in Citrus reticulata and its anthelmintic effect. Method: Various concentration of Methanolic extract and Volatile oil of Citrus reticulata were subjected for assessment of anthelmintic activity in earthworms. Time of paralysis and time of death were used as an evaluation parameter. Albendazole (25 mg/ml) was used as a standard drug. Results: Phytochemical test revealed the presence of alkaloids, carbohydrates, tannins, flavonoids, terpenoids and glycosides. Concentration dependent anthelmintic effect was observed with the extract where 150 mg/ml concentration of methanolic extract showed paralysis of test worm (earthworm) at 5.76 min and death at 19.16 min respectively. Conclusion: Citrus reticulata peel has shown substantial anthelmintic activity using in vitro model on earthworms. Hence, further research is required to understand its mechanism of action using in vivo models to confirm its anthelmintic potential.